A survey instrument design to determine the success factors in implementing the end-of-life vehicles (ELVs) management system in Malaysia - Raja Mamat, Tengku Nur Azila; Mat Saman, Muhamad Zameri; Sharif, Safian (Trans Tech Publications, 2015)
This paper presents the design of a survey instrument in order to determine the success factors in implementing the end-of-life vehicles (ELVs) management system in Malaysia. Upon reviewing journal articles and research papers previously conducted in automotive recycling, end of-life vehicles, success factors and green supply chain, a set of preliminary factors was identified.These factors were categorized into seven components, namely the government commitment,stakeholders commitment, resources availability, enforcement and monitoring, education and awareness, market structure and continuous improvement. Thirty items were listed in the questionnaire, where the statements were based on the above said seven factors. Other than that,target respondents and sampling size were also discussed.